Positive solutions of higher order fractional integral boundary value problem with a parameter - Hao, Xinan; Zhang, Luyao; Liu, Lishan (Nonlinear Analysis: Modelling and Control, 2019)
In this paper, we study a higher-order fractional differential equation with integral boundary conditions and a parameter. Under different conditions of nonlinearity, existence and nonexistence results for positive solutions are derived in terms of different intervals of parameter. Our approach relies on the Guo–Krasnoselskii fixed point theorem on cones.